2013
DOI: 10.1007/s13744-013-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Sugarcane Cultivars to Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae)

Abstract: The spittlebug Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) is one of the most important pests of the sugarcane crop in Brazil. Despite of its importance, there is currently a lack of information regarding sugarcane cultivars' resistance to the spittlebug. Therefore, our objective was to evaluate the response of sugarcane genotypes to this species. Two experiments were carried out under laboratory conditions using a random block design with treatments in a factorial arrangement of 2 × 13 (experiment 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
3
25
0
1
Order By: Relevance
“…The author recorded that spittlebug nymph attacks on sugarcane reduce leaf chlorophyll content and, consequently, the photosynthetic rate, with a decrease in plant production. These facts were observed in the present work and by Dinardo-Miranda et al (2014) Table 5. Multiplication rate of Mahanarva fimbriolata each 39 days for each cultivar.…”
Section: Cultivar Eggs Per Plant Eggs Viability (%)supporting
confidence: 90%
See 3 more Smart Citations
“…The author recorded that spittlebug nymph attacks on sugarcane reduce leaf chlorophyll content and, consequently, the photosynthetic rate, with a decrease in plant production. These facts were observed in the present work and by Dinardo-Miranda et al (2014) Table 5. Multiplication rate of Mahanarva fimbriolata each 39 days for each cultivar.…”
Section: Cultivar Eggs Per Plant Eggs Viability (%)supporting
confidence: 90%
“…The degree of susceptibility, however, varied among cultivars: RB966928 was the less susceptible, presenting 19.0% of aboveground biomass reduction, while RB935744 was one of the most susceptible, showing 70.4% of aboveground biomass reduction due to pest attack (Table 7). Dinardo-Miranda et al (2014; also found different tolerance degrees among sugarcane cultivars, some of them could be considered tolerant, as IACSP96-7569, for example.…”
Section: Cultivar Eggs Per Plant Eggs Viability (%)mentioning
confidence: 96%
See 2 more Smart Citations
“…Cultivar SP81-3250 was chosen as a susceptible reference cultivar (Dinardo-Miranda et al, 2001) that is widely cultivated in São Paulo State, Brazil, and the others were chosen…”
Section: Methodsmentioning
confidence: 99%